Hei-Ho! - Davies, Daniel (Y Lolfa, 2009)
A humorous novel by the author of Gwylliaid Glyndŵr and the book of short stories, Twist ar Ugain. This novel is set in Aberystwyth and features many colourful characters. The story follows seven people who were made redundant due to what is called 'a financial squeeze'. Intro – RHAN 1 – 1 – 2 – 3 – 4 – 5 – 6 – RHAN 2 – 1 – 2 – 3 – 4 – 5 – 6 – RHAN 3 – 1 – 2 – 3 – 4 – 5 – 6 – 7 – RHAN 4 – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – RHAN 5 – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – RHAN 6 – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – RHAN 7 – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – 11 – 12 – 13 – 14 – 15 – 16 – 17 – 18 – RHAN 8 – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – 11 – 12 – 13 – 14 – 15 – 16 – 17 – 18 – 19 – 20 – 21 – 22 – 23 – 24 – 25 – 26 – 27 – 28.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books